Caracterização mineralógica de um Neossolo Flúvico por técnicas de espectroscopia, microscopia e difração de raio X - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The soil is one of the most important resources for the survival of live beings. It can be used for both food production and as the survival environment, which makes it susceptible to constant action, and it develops throughout time due to several factors such as original material, climate, geographical location, etc. Soils can present properties that differ one from another. One of the reasons for knowing the soil properties is related to the environmental issue, since knowing its behavior will enable solutions or reduction in problems that might impact the environment. One of the existing degrading processes is erosion due to the use of the soil. This occurred in a rural area in the south of Baliza-GO. This process originated a new soil, classified as Fluvisol, which is formed by the horizons A, C1, C2 and C3, studied in this research. The mineralogical characterization of the Fluvisol was carried out, particle density was determined and the soil texture was classified. Physical fractioning was performed to separate the fractions sand, silt and clay. The air dried fine soil and the fractions were submitted to elemental analysis using Energy Dispersive X-Ray Fluorescence spectroscopy and Wavelength Dispersive X-Ray Fluorescence spectroscopy. The qualitative analysis using Fourier Transformation Infrared spectroscopy and X- Ray Diffraction identified the following minerals: calcite, Kaolinite, gibbsite, illite, magnetite, montmorillonite, quartz and rutile. Other techniques were also used to investigate the clay fraction such as Dynamic Light Scattering, Atomic Force Microscopy and Emission Scanning Electron Microscopy - Field Emission Gun, which allowed the observation of sizes, distributions and the shapes of the minerals found. Finally, the Rietveld Method was used to quantify the minerals in that fraction. Horizon A presented results that were compatible to the original sediments in relation to particle density (2.615 g/cm3 ) and soil texture (sandy loam). Considering the minerals present, there was compatibility between the horizons A, C1 and C2 (calcite, Kaolinite, gibbsite, illite, magnetite, montmorillonite, muscovite, quartz and rutile), while horizon C3 was shown to be different (calcite, kaolinite and quartz). The clay fraction particles, which can reach up to 2 µm, showed particle-sizes smaller than 1 µm. The mineral kaolinite was the mineral presenting the highest amount in the clay fraction regarding horizons A, C1 and C2: 44.6 %, 50.7 % and 65.8 %, respectively, and it was the easiest to identify one of its possible shapes, hexagonal. Therefore, it was possible to characterize the Fluvisol in this study regarding particle density, textural analysis and mineralogy, by focusing on the clay fraction.
Keywords: Densidade de partícula; Análise textural; Fração argila; Análise elementar; Método de Rietveld; Particle density; Textural analysis; Clay fraction; Elemental analysis; Rietveld Method; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA